ANTECEDENTS OF STOCK INVESTMENT INTENTION AMONG GENERATION Z - Anjelika Natasyah; Ali Wardhana (Journal of Business And Entrepreneurship, 2026)
This study examines how financial literacy, attitude toward investment, subjective norms, and perceived behavioral control relate to stock investment intention among Generation Z. A quantitative survey design was used, with data gathered from 222 Generation Z respondents through purposive sampling and analyzed with Structural Equation Modeling-Partial Least Squares (SEM-PLS) in SmartPLS 4.0. Attitude toward investment, subjective norms, and perceived behavioral control each showed a positive and significant relationship with investment intention, and financial literacy likewise had a significant effect. The results add to what is known about financial management among younger investors and offer a point of reference for investors, financial institutions, and researchers examining the drivers of stock investment intention.